PEMANFAATAN MEDIA FLIPCHART VARIASI OLAHAN IKAN BANDENG DAN UDANG UNTUK MENUMBUHKAN WIRAUSAHA BIDANG BOGA (FOODPRENEUR) PADA REMAJA - Yulianti, Yeni; Artanti, Guspri Devi; Putri, Dyah Ayu Kensasmi; Sabrina, Fildzah Zharifah Nur (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The flipchart media is used to improve the entrepreneurial skills of students of SMAN 1 Muara Gembong, supporting school programs such as entrepreneurship and the Pancasila Student Profile Strengthening Project (P5). The instrument used was a questionnaire to assess the quality of training media and satisfaction with the implementation of activities. The method used was training with data analysis of quantitative descriptive techniques. Product trials were conducted at the Processing Laboratory of the Catering Study Programme, Faculty of Engineering, State University of Jakarta, to find the best product formulation for fishrimp seaweed roll, fish finger, fish gyoza, fish egg roll, fish cake, milkfish spring roll, fried noodles, milkfish croquette, and serundeng talam cake. The media used was a flipchart containing information about milkfish, entrepreneurship, selling price calculation, processed product recipes, packaging examples, and labels. The training was attended by 30 students, the vice principal, teacher representatives, and school canteen managers. The quality assessment of the training media was 100% positive, with a satisfaction rating of 76.89% stating very satisfied, 18.603% stating satisfied, and 4.05% stating moderately satisfied from a total of 30 participants. The flipchart media can be used to increase the youth’s knowledge and skills, foster creativity in product innovation, and encourage entrepreneurial spirit, especially about processed milkfish and shrimp variations.